W poszukiwaniu tożsamości. Lwów w twórczości Adama Zagajewskiego - Czajkowska, Zoriana (Postscriptum Polonistyczne, 2020)
The paper devoted to an important theme in Adam Zagajewski’s work: the search for identity. Using the author’s biography as the background, the author of the paper refers to various works by the writer (including Two Cities, To Go to Lvov, and Should We Visit Sacred Places?) and draws attention to the fact that the author’s poetic declaration about homelessness is his identity status; consequently, the author of the paper focuses on the aspect of Lviv in Zagajewski’s work.